Meniscus‐Guided Micro‐Printing of Prussian Blue for Smart Electrochromic Display (Adv. Sci. 3/2023). Issue 3 (25th January 2023) - Kim, Je Hyeong; Park, Seobin; Ahn, Jinhyuck; Pyo, Jaeyeon; Kim, Hayeol; Kim, Namhun; Jung, Im Doo; Seol, Seung Kwon
Abstract : Meniscus‐Guided Printing Meniscus‐guided micro‐printing of Prussian Blue is realized by the localized crystallization of FeFe(CN)6 on the substrate confined by the ink meniscus and thermal reduction of the crystallized FeFe(CN)6 . This strategy is capable of being used as an electrochromic display to give real‐time directions on an augmented reality (AR) smart contact lens device. More details can be found in article number 2205588 by Im Doo Jung, Seung Kwon Seol, and co‐workers.